2012
DOI: 10.1620/tjem.228.223
|View full text |Cite
|
Sign up to set email alerts
|

Eradication Therapy Is Effective for <i>Helicobacter pylori</i>-Negative Gastric Mucosa-Associated Lymphoid Tissue Lymphoma

Abstract: Mucosa-associated lymphoid tissue (MALT) lymphomas are extra-nodal B-cell lymphomas arising from MALT, and the most commonly affected organ is the stomach. Helicobacter pylori (H. pylori) eradication therapy with proton-pump inhibitors and antibiotics is the first-line therapy for H. pylori-positive gastric MALT lymphomas, but the effectiveness of the therapy for H. pylori-negative gastric MALT lymphomas remains controversial. Hence, we aimed to evaluate the effectiveness of this eradication therapy for H. pyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 17 publications
(22 reference statements)
0
22
2
Order By: Relevance
“…This was the highest reported response rate among H. pylori-negative gastric MALT lymphomas. The response rate decreased to 46% in their later study [52] , but this was still relatively high compared with other reports [3,[46][47][48][49][50] . Contrary to these reports, earlier studies reported that H. pylorinegative gastric MALT lymphomas did not respond to antibiotic therapy [14,30,45] .…”
Section: Treatmentcontrasting
confidence: 53%
See 3 more Smart Citations
“…This was the highest reported response rate among H. pylori-negative gastric MALT lymphomas. The response rate decreased to 46% in their later study [52] , but this was still relatively high compared with other reports [3,[46][47][48][49][50] . Contrary to these reports, earlier studies reported that H. pylorinegative gastric MALT lymphomas did not respond to antibiotic therapy [14,30,45] .…”
Section: Treatmentcontrasting
confidence: 53%
“…Nonetheless, further studies are warranted to clarify the cause underlying this discrepancy. Regarding the predictive factor for responsiveness, multiple lesions [49] , lesions in both proximal and distal parts of the stomach [50] , and the presence of t(11;18)(q21;q21) [50] were predictive factors for nonresponsiveness to antibiotic therapy. We have previously reported that 5 out of 17 H. pylori-negative gastric MALT lymphoma patients treated with antibiotics and PPI responded to the therapy, and 3 out of 5 responders had single lesions, while all non-responders had multiple lesions [49] .…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, several studies have also demonstrated success in H. pylori therapy for some H. pylori negative MALT lymphoma patients [17,18] implicating other aetiologies in the development of MALT lymphoma.…”
Section: Discussionmentioning
confidence: 99%